Effects of citrate-stabilized gold and silver nanoparticles on some safety parameters of Porphyridium cruentum biomass - Rudi, Ludmila; Cepoi, Liliana; Chiriac, Tatiana; Miscu, Vera; Valuta, Ana; Djur, Svetlana (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Our research raises the question of how realistic and safe it is to use gold and silver nanoparticles in biotechnologies to grow microalgae, which will later be used to obtain valuable products. To this purpose, it was necessary to assess the influence of 10 and 20 nm Au and Ag nanoparticles stabilized in citrate on the growth of microalga Porphyridium cruentum in a closed cultivation system, as well as some safety parameters of biomass quality obtained under experimental conditions. Methods: Two types of experiments were conducted with the addition of nanoparticles on the first day and the fifth day of the cultivation cycle. Changes in productivity, lipid content, malondialdehyde (MDA), as well as antioxidant activity of microalgae biomass have been monitored in dynamics during the life cycle in a closed culture system. Results: The impact of nanoparticles on the growth curve of microalgae culture was marked by delaying the onset of the exponential growth phase. A significant increase in the content of lipids and MDA in biomass was noted. Excessive accumulation of lipid oxidation products within the first 24 h of cultivation resulted in altered antioxidant activity of red algae extracts. Discussion: Citrate-stabilized gold and silver nanoparticles proved to be a stress factor for red microalga Porphyridium cruentum, causing significant changes in both biotechnological and biomass safety parameters. Addition of Au and Ag nanoparticles during the exponential growth phase of porphyridium culture led to an enhanced lipid accumulation and reduced MDA values in biomass.